1975
DOI: 10.1111/j.1365-2265.1975.tb01565.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Testosterone and Prolactin in the Menstrual Cycle

Abstract: Daily hormonal studies during nine ovulatory menstrual cycles showed that plasma prolactin and testosterone concentrations fluctuated randomly and independently. Mean plasma testosterone levels were found to be higher during the 7 days before and after the mid-cycle LH peak when compared to the premenstrual phase (P less than 0-01). No correlation was found between daily levels of prolactin and those of LH, FSH, oestrogen or progesterone and no correlation was seen between peaks of prolactin and testosterone o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
8
0
1

Year Published

1977
1977
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 19 publications
(8 reference statements)
4
8
0
1
Order By: Relevance
“…Some women had an increased nocturnal plasma PRL level at midcycle, but the peak level at this time was not significantly different for the group as a whole. This finding is in agreement with other reports (26)(27)(28)(29) which reported that some, but not all, women have increased plasma PRL levels at midcycle. The small, early evening peak in plasma PRL levels that was evident in most of our subjects has also been observed previously (29,30).…”
Section: Discussionsupporting
confidence: 95%
“…Some women had an increased nocturnal plasma PRL level at midcycle, but the peak level at this time was not significantly different for the group as a whole. This finding is in agreement with other reports (26)(27)(28)(29) which reported that some, but not all, women have increased plasma PRL levels at midcycle. The small, early evening peak in plasma PRL levels that was evident in most of our subjects has also been observed previously (29,30).…”
Section: Discussionsupporting
confidence: 95%
“…In 1972, Vekemans et al using a radioimmunoassay (3) described a biphasic pattern of serum prolactin concentration during the menstrual cycle: there was a distinct midcycle peak and during the luteal phase the levels fluctuated around an average value significantly higher than during the early follicular phase. Some investigators reported similar changes (4-7), but others did not observe any significant variation in circulating prolactin during the cycle (8)(9)(10)(11)(12)(13). In this study, involving a larger series of cycles we confirmed our previous observations (3).…”
Section: Discussionsupporting
confidence: 94%
“…In women, circulating prolactin has been measured during the menstrual cycle by several investigators. Contradictory data were reported (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The purpose of this study was to Received October 6, 1976.…”
mentioning
confidence: 90%
“…Some investigators have failed to observe any systemic fluctuation on prolactin levels during the cycle (Ehara et al, 1973, McNeilly and Chard 1974, Epstein et al, 1975, while recent reports, referred to an overall pattern of serum prolactin during the menstrual cycle which resembled that for circulating estradiol (Franchimont et al, 1976, Vekemans et al, 1977, Djursing et al, 1981, Minakami et al, 1985 with small differences between the prolactin levels in the follicular and luteal phases.…”
mentioning
confidence: 99%